Nitric oxide inhalation decreases pulmonary artery remodeling in the injured lungs of rat pups - Roberts, Jesse D.; Chiche, Jean-Daniel; Weimann, Jörg; Steudel, Wolfgang; Zapol, Warren M.; Bloch, Kenneth D. (Circulation research, 2000)
—Vascular injury causes the muscularization of peripheral pulmonary arteries, which is more pronounced in the infant than in the adult lung. Although inhaled NO gas attenuates pulmonary artery remodeling in hypoxic rats, whether or not it protects the lung by mitigating vasoconstriction is unknown. This investigation tested whether inhaled NO decreases the muscularization of injured pulmonary arteries in rat pups by modulating vascular tone. One week after monocrotaline administration, the percentage of muscularized rat pup lung arteries was increased by >3-fold. Nevertheless, monocrotaline exposure did not cause right ventricular hypertrophy, pulmonary hypertension, or vasoconstriction. In addition, it did not increase the expression of markers of inflammation (interleukin-1β, intercellular adhesion molecule-1, and E-selectin) or of platelet-mediated thrombosis (GPIbα). Continuous inhalation of 20 ppm NO gas prevented the neomuscularization of the pulmonary arteries in pups with lung injury. Moreover, a 3-fold increase in cell proliferation and 30% decrease in cell numbers in pulmonary arteries caused by monocrotaline exposure was prevented by NO inhalation. These data indicate that inhaled NO protects infants against pulmonary remodeling induced by lung injury by mechanisms that are independent of pulmonary tone, inflammation, or thrombosis. (Circ Res. 2000;87:140-145.)
Gesehen am 11.01.2022